2021
DOI: 10.2147/ijgm.s331864
|View full text |Cite
|
Sign up to set email alerts
|

Causal Relationships Between Social Isolation and Osteoarthritis: A Mendelian Randomization Study in European Population

Abstract: Objective:We aimed to investigate the causal relationships between social isolation and osteoarthritis. Methods: Publicly available genome-wide association study (GWAS) summary statistics of social isolation and osteoarthritis in European population were obtained from the Neale lab Consortium and the Medical Research Council-Integrative Epidemiology Unit (MRC-IEU) consortium, respectively. Single nucleotide polymorphisms (SNPs) associated with the traits were identified by P < 5×10 −8 and linkage disequilibriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Further analyses revealed these associations to be partially, although not completely, mediated by BMI and smoking. Genetically predicted levels of social isolation were associated with higher OA risk in the study by Zheng et al (OR 1.20, 95% CI 1.10–1.31) 49 . This study used a five SNP instrument to proxy social isolation, and sensitivity analyses revealed no evidence for pleiotropy.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Further analyses revealed these associations to be partially, although not completely, mediated by BMI and smoking. Genetically predicted levels of social isolation were associated with higher OA risk in the study by Zheng et al (OR 1.20, 95% CI 1.10–1.31) 49 . This study used a five SNP instrument to proxy social isolation, and sensitivity analyses revealed no evidence for pleiotropy.…”
Section: Resultsmentioning
confidence: 73%
“…Genetically predicted levels of social isolation were associated with higher OA risk in the study by Zheng et al (OR 1.20, 95% CI 1.10-1.31). 49 This study used a five SNP instrument to proxy social isolation, and sensitivity analyses revealed no evidence for pleiotropy. Mediation analyses were not performed to evaluate the mechanism through which social isolation might increase OA risk.…”
Section: Resultsmentioning
confidence: 95%
“…Supplementary material 1 showed the SNP information of four exposures (intake of processed meat, pork, beef and mutton), consisting of the name, chromosome location, genes, function, effect allele (EA), other alleles, and effect allele frequency (EAF). We calculated the F statistic for instrumental variable selection and F statistics were >10, which indicated that we have effectively avoided the bias caused by weak instrumental variables ( Supplementary material 1 ) ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
“… 6 Clinical studies, on the other hand, have indicated that those who are socially isolated are more prone to experience pain, such as muscular and joint pain. 20 , 21 For the first time, we examined the impact of social isolation on visceral pain sensitivity. In contrast to the effect of social isolation on somatic pain, social isolation increased the sensitivity of rats to visceral pain.…”
Section: Discussionmentioning
confidence: 99%